Asymmetric synthesis of moiramide B - Dixon, D; Davies, S (1996)
The first asymmetric synthesis of Moiramide B 1 is achieved using lithium amide 4 and pyrrolidinone auxiliary 5; pyrrolidinone auxiliary 5 is used to create the novel (S)-2-methyl-N-benzyloxysuccinimide 15 which is subsequently acylated with the highly reactive tert-butoxycarbonyl-protected N-carboxanhydride of L-valine (Boc-Val-NCA) under strongly basic conditions, without racemization, while lithium amide 4 is used to synthesize homochiral D-β-phenylalanine tert-butyl ester 8.